CFD Characteristics of Refrigerated Trailers and Improvement of Airflow for Preserving Perishable Foods - Turkay Yildiz (Logistics)
When preserving perishable goods, maintaining a constant temperature over the cold supply chain is essential. Therefore, refrigerated vehicles are an important part of the cold supply chain system. However, many traditional refrigerated cargo systems are not designed to support the homogeneity of the temperature inside cargo trailers. Indeed, refrigerating equipment is usually placed on one side of transportation systems as this is considered to be more practical. Such a configuration thus leads to significant temperature differences in the two distinct parts of a refrigerated cargo trailer, which might affect the quality, safety, and shelf life of perishable foods. This research aims to improve the temperature distribution of refrigerated trailers. In this study, it is highlighted that in the most commonly used traditional refrigerated trailer models, lower air velocity and higher product temperature are observed at the rear. There is also a partial product chilling risk at the front of the refrigerated trailer. This study investigates and reports significant differences among the three airflow design models of refrigerated cargo systems by applying turbulence flow, heat, and mass transfer models. The analyses of these three models reveal that significant improvement could be achieved by applying the proper arrangements of inlets on the ceiling of the trailer body.